Graphic design basics - Arntson, Amy E. (Wadsworth, Cengage Learning, 2012)
Combines design principles, history, and technology to present students a comprehensive introduction to the field of graphic design. This text emphasizes design structure, visual perception and digital design, with a wide range of visuals from throughout design history, as well as the contemporary illustrations.